(untitled) (Research, Society and Development, 2022)
The social isolation experienced during the Sars-cov-2 pandemic revealed a significant increase in the use of electronic equipment worldwide. New problems were highlighted thanks to this increase, especially in sleep. Increases of up to 10 hours a day in the use of electronics were observed, due to work and studies that started to happen remotely. In this context, this study aimed to evaluate the relationship between electronics use and sleep disorders during the Covid-19 pandemic. This is a descriptive, observational study with a cross-sectional design that gathered information provided by the population of the southern region of Brazil. Data collection was carried out through an online questionnaire using the Google Forms tool, composed of twenty-two questions and applied in the first half of 2021. Descriptive statistics of frequency, position and dispersion were used to analyze the data. In all, 289 responses were obtained. Reports point to a significant increase in device use during the pandemic. It is also noted that 32.5% of respondents have some sleep disorder. A predominance of insomnia was noticed in 24.5% of the sample. These disorders may be related to the increase in the daily use of electronic devices. The relevance of a deeper understanding of the relationship between the use of electronic devices and sleep disorders during the Covid-19 pandemic is highlighted.